The white tiger : a novel - Adiga, Aravind (New Delhi : Harper Collins Publishers, 2008)
Balram Halwai is a complicated man. Servant. Philosopher. Entrepreneur. Murderer. Over the course of seven nights, by the scattered light of a preposterous chandelier, Balram tells the terrible and transfixing story of how he came to be a success in life -- having nothing but his own wits to help him along.
Keywords: Chauffeurs -- India -- Bangalore -- Fiction; Poor -- India -- Bangalore -- Fiction; Ambition -- Fiction; Business people -- India -- Bangalore -- Fiction; Bangalore (India) -- Fiction; Epistolary fiction; Mystery fiction